Child-to-Parent Violence and Dating Violence Through the Moral Foundations Theory: Same or Different Moral Roots? - Vecina, Maria L.; Chacón, Jose C.; Piñuela, Raúl (Frontiers in Psychology, 2021)
The objective of this study is exploratory and seeks to verify the utility of the five moral foundations (care, fairness, loyalty, authority and purity) to differentiate between two understudied groups, namely young offenders who use violence against their parents or dating partners, as well as to predict the extent to which these young people justify violence and perceive themselves as aggressive. Although both types of violence imply, by definition, harming someone (low care) and adopting a position of authority (high authority), we hypothesize a very different role for at least these two moral foundations. Our results support this idea and show a much lower regard for the five moral foundations, including care and authority, in the Child to Parent Violence group (CPV; N = 65) than in the Dating Violence group (DV; N = 69). Additionally, the authority foundation was able to increase the effectiveness of correctly classifying the participants in one group or the other by 29%. Finally, care and authority, along with fairness, served to predict justification of violence and self-perceived aggressiveness. The moral foundations approach provides preliminary evidence to better understand two specific types of youth violence and extract preventive educational and treatment strategies.